ChemInform Abstract: Formal Synthesis of Sarain A: Intramolecular Cycloaddition of an Eight‐Membered Cyclic Nitrone to Construct the 2‐Azabicyclo[3.3.1]nonane Framework. Issue 43 (October 2015) - Higo, Takuya; Ukegawa, Tomoya; Yokoshima, Satoshi; Fukuyama, Tohru
Abstract A synthetic route to the tetracyclic skeleton of sarain A is developed, featuring an intramolecular cycloaddition of an eight‐membered cyclic nitrone to construct the 2‐azabicyclo[3.3.1]nonane framework and an iodoamidation reaction to form the pyrrolidine ring.